A case study on issues related to ethnic diversity in a small ad hoc group - Saravella, Sunday (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study explores the issues related to ethnic diversity in small ad hoc group among students in Universiti Malaysia Sarawak (UNIMAS). An in-depth interview method was used as a main source for data collection to elicit in-depth information from the respondents. Documentary analysis was also carried out to enhance the findings of this research. Due to time constraints, limited respondents were interviewed, the researcher only managed to interview six respondents, which is still acceptable since the nature of the research are exploratory and descriptive. The findings from this study could be limited but yet interesting as the study on this issue is still rare. Findings indicated that the perceptions of students towards diversity are willing to work, develop openness and acceptance of ideas from others. The benefits from working in a diverse small ad hoc group are knowledge of others culture, different life experience, respect, develop tolerance, widen networking/relationship, develop cooperation and increase creativity. Sometimes, there are drawbacks from working in diverse group such as lack of communication lead to failure, no acceptance for others opinions, miscommunication and no understanding. The various efforts contributes by group members and group leaders are compromise, respect others opinion, do not touch on religion, avoid mentioning sensitive issues and tolerate with other members.